2016
DOI: 10.1007/s12040-016-0735-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wind speed on surface layer stability and turbulent fluxes over southern Indian peninsula station

Abstract: Surface to atmosphere exchange has received much attention in numerical weather prediction models. This exchange is defined by turbulent parameters such as frictional velocity, drag coefficient and heat fluxes, which have to be derived experimentally from high-frequency observations. High-frequency measurements of wind speed, air temperature and water vapour mixing ratio (eddy covariance measurements), were made during the Integrated Ground Observation Campaign (IGOC) of Cloud Aerosol Interaction and Precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Equation indicates that C DN should be independent of wind speed for a fixed z 0 . However, observations show that C DN increases sharply with the decrease of wind speed in light winds (Al‐Jiboori, 2010; Grachev et al., 2006; Mahrt et al., 2015; Patil et al., 2016; Rao, 2004; Rao et al., 1996). The behavior of C DN in light winds, which is in excess of that expected by MOS theory and may affect the performance of the weather and climate numerical models, has attracted increasing attention (Katz & Zhu, 2017; Mahrt, 2008; Srivastava & Sharan, 2015; Zhu & Furst, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Equation indicates that C DN should be independent of wind speed for a fixed z 0 . However, observations show that C DN increases sharply with the decrease of wind speed in light winds (Al‐Jiboori, 2010; Grachev et al., 2006; Mahrt et al., 2015; Patil et al., 2016; Rao, 2004; Rao et al., 1996). The behavior of C DN in light winds, which is in excess of that expected by MOS theory and may affect the performance of the weather and climate numerical models, has attracted increasing attention (Katz & Zhu, 2017; Mahrt, 2008; Srivastava & Sharan, 2015; Zhu & Furst, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…the surface, and it plays an important role in the transport of momentum in the boundary layer. Patil et al (2016) reported that the frictional velocity increases with increasing wind speed under lower wind speed conditions in the surface layer. Thus, we focused on the variations in the wind speed (Figs.…”
Section: Effects Of Patch-induced Circulation On the Turbulent Intensity And Heat Fluxmentioning
confidence: 99%
“…The frictional velocity (u * ) is a critical parameter in the turbulence exchange near the surface, and it plays an important role in the transport of momentum in the boundary layer. Patil et al (2016) reported that the frictional velocity increases with wind speed under lower wind speed conditions in the surface layer. Thus, we focused on the variations in the wind speed (Fig.…”
Section: Turbulence In the Surface Layermentioning
confidence: 99%